Comparative histology of the digestive tract in three new world marsupials. (3rd January 2018) - Andrini, Laura Beatríz; García, Marcela Nilda; Inda, Ana María; Errecalde, Ana Lía; Goin, Francisco J; Carlini, Alfredo Armando; Scarano, Alejo Carlos; Martin, Gabriel; de los Reyes, Martín
Abstract: We compare the main histological features of the digestive tract of three selected New World didelphid marsupials (Mammalia, Metatheria, Didelphimorphia, Didelphidae): the White‐eared Opossum Didelphis albiventris Lund, 1840, the Short‐tailed Opossum Monodelphis dimidiata Wagner, 1847, and the Patagonian Opossum Lestodelphys halli Thomas, 1921. The three species have a geographic distribution restricted to south‐eastern and southern South America, and have quite distinct body masses, adaptations and life histories. Our observations include the following: (i) submucosal glands are present throughout the oesophagus of D. albiventris, only in its first third in M. dimidiata, and are lacking in L. halli ; (ii) in the stomach and duodenum, the serus coat coat in D. albiventris is cuboidal (simple, squamous mesothelial layer in the other two species); (iii) the duodenum in L. halli has large folds, short crypts and Brunner's glands (the other species lack folds and Brunner's glands); (iv) the colon's mucous membrane has short, scarce villi in D. albiventris (villi absent in the remaining species). Some of the observed differences can be due to ecological adaptations, especially in the relatively large‐sized, extremely omnivorous D. albiventris (e.g., colon villi).